Clinicopathologic and Proteomic Analysis of Amyloidomas Involving the Ocular Surface and Adnexa. Issue 4 (26th October 2021) - Jamshidi, Pouya; Levi, Jonathan; Suarez, Maria Jose; Rivera, Roxana; Mahoney, Nicholas; Eberhart, Charles G; Rosenberg, Avi; Rodriguez, Fausto J
Abstract: Objectives: Ocular amyloidoma is a rare disorder characterized by deposition of insoluble proteinaceous fibrils in the extracellular space of the ocular adnexa. This study details the clinicopathologic features and proteomic characteristics of periocular amyloid deposition. Methods: Specimens (1991-2020) were retrieved and reviewed. All available H&E slides and special stains were reviewed. Proteomic analysis was performed using immunohistochemistry (IHC) for IgG, IgG4, IgA, IgD, IgM, CD20, CD3, CD138, and κ/λ, as well as chromatography-electrospray tandem mass spectrometry on formalin-fixed, paraffin-embedded tissue. Results: There were 14 patients (7 men, 7 women). The depositions involved eyelid (n = 3), conjunctiva (n = 8), and orbit (n = 3). All patients were adults with a median age at diagnosis of 56 (range, 39-88) years. The deposits were predominantly λ light chain restricted (n = 6) and mixed light chains (n = 2), and one case was κ predominant. Two of the cases with a mixture of κ and λ light chains had an excess of transthyretin by mass spectrometry. Four of the cases did not have adequate material for proteomic subtyping. Conclusions: Amyloidomas involving ocular adnexa contain a variety of amyloid-related and immunoglobulin-associated peptides. The λ light chain predominates as in other body sites, but mixed patterns and rarely κ light chain restriction may be encountered.